Too good to eat? Cosmetic standards and waste in agricultural supply chain - XU, Jiahui (Institutional Knowledge at Singapore Management University, 2020)
There is a significant amount of food wasted at the farm level due to high cosmetic standards adopted by retailers. We examine the economic incentives for retailers to adopt such high cosmetic standards and their impact on food loss. We build a sequential game between a retailer and a farmer, where the retailer signs a contract with the farmer specifying both the wholesale price and cosmetic quality standard. By adopting high cosmetic standards, retailers can motivate farmers to exert a higher effort to improve the cosmetic quality, e.g., using better seeds and applying more pesticides. As for the drivers of high cosmetic standards, we find an increase in customers' willingness-to-pay for aesthetically pleasing produce induces the retailer to adopt a higher standard or a lower standard. The retailer is more likely to adopt a higher cosmetic standard when the unit price in the processing market increases. The impact of harvesting cost variability on optimal cosmetic standard is non-monotonic. As for food loss, we find that a higher cosmetic standard does not necessarily lead to a higher food loss.